Effect of Exercise Training Program in Pain, Muscle Strength and Functional Mobility in Post Cervical Decompression Surgeries - Kamble Jyotsna Prabhakar1, Kanase Suraj B2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Cervical disease is caused by various factors like degeneration, disc protrusion. According to previous studies, there are 20 – 30% patients with cervical disc disease. There are various complications according to the level of lesions. Cervical disc diseases are the condition which affects the motor and sensory components of the body. This study specially emphasis on the sensory and motor components. This study focuses on the stage wise progression of the patient. The patients also have reduced functional ability. This study emphasis on the increasing the functional ability of the patients. Greater efficacy of rehabilitation can be brought about by early intervention for improving strength and increase sensory integration which might achieve activities of daily living goals. Aim: To find the effect of exercise training program in patients with cervical decompression surgeries. Methodology: There were 35 participants in the study. The type of study is experimental. The participants involved were assessed for strength, pain and functional mobility. The participants are treated for pain, strength and functional mobility. Result: There is improvement seen in participants. The results of the participants are calculated by mean and standard deviation. The pre assessment is 56% and post assessment is 38% percentage for pain. The pre assessment is 1.74% and post assessment is 3.31% percentage for functional mobility. The pre assessment is 23.4% and post assessment is 50.8% percentage for right upper limb strength. The pre assessment is 23.2% and post assessment is 42.8% percentage for right lower limb strength. The pre assessment is 23.4% and post assessment is 48% percentage for left upper limb strength.The pre assessment is 23.4% and post assessment is 41.7% percentage for left lower limb strength. The pre assessment is 13.7% and post assessment is 42.8% percentage for trunk strength. Conclusion: Structured exercises programis effective in reducing pain and improving muscle strength and functional mobility in patients with post cervical decompression surgeries.